2020
DOI: 10.1186/s12905-020-00923-9
|View full text |Cite
|
Sign up to set email alerts
|

Modern contraceptive utilization and associated factors among reproductive-age women in Ethiopia: evidence from 2016 Ethiopia demographic and health survey

Abstract: Background: Modern contraceptive methods enable couples to enjoy sexual intercourse without fear of the risk of pregnancy at any desired time. The evidence from different studies done in Ethiopia on modern contraceptive method utilization was highly varied and not conclusive. Therefore, the current study aims to study the magnitude of modern contraceptive utilization and associated factors among reproductive-age women in Ethiopia based on 2016 EDHS data. Method: A nationally representative 2016 EDHS data colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
51
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 22 publications
(59 reference statements)
24
51
9
Order By: Relevance
“… 41 We also observed in our study that nulliparous women were less likely to use CPs than parous women. This finding is consistent with previous studies, 16 42 but contrary to the findings of Geremew and Gelagay. 34 …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“… 41 We also observed in our study that nulliparous women were less likely to use CPs than parous women. This finding is consistent with previous studies, 16 42 but contrary to the findings of Geremew and Gelagay. 34 …”
Section: Discussionsupporting
confidence: 88%
“…41 We also observed in our study that nulliparous women were less likely to use CPs than parous women. This finding is consistent with previous studies, 16 42 but contrary to the findings of Geremew and Gelagay. 34 In the results, we reported that women resident in rural settings were associated with reduced use of CPs compared with their colleagues from urban settings.…”
Section: Discussionsupporting
confidence: 87%
“…Women who were sexually active four weeks before the survey were 3.614 times more likely to use a modern contraceptive method than women who were sexually inactive in the last 4 weeks. Also, the study veri ed that respondents education level, husband/partner's educational level, age difference between husband and women, and mass media exposure were signi cantly associated with modern contraceptive use in the bivariate analysis but have no statistical signi cant association after controlling for potential confounders (Table 2 ; which is consistent with results from Ethiopia and Zambia [13,16,17]. However, we found that there was no signi cant association between women aged (20-24 years) and contraceptive use.…”
Section: Binary Logistic Regressionssupporting
confidence: 80%
“…Previous studies have considered the determinants of contraceptive use in Ethiopia [12,13]. In most of the previous studies, complex sampling design is not considered and since this data is from multistage sampling, which involves the use of different strata, clustered sampling techniques and unequal selection probabilities, it is inappropriate to conduct analysis without taking the survey sampling designs into account.…”
Section: Introductionmentioning
confidence: 99%
“…A woman was deemed to be a modern contraceptive user if she uses at least one of the following methods: female sterilization, male sterilization, IUD, injectable, implants, pills, male condom, female condom, emergency contraception, and standard days method. On the other hand, non-users are those who resort to the use of traditional methods such as rhythm method, lactation amenorrhea method, and withdrawal or if she had not been using any type of contraception at all [ 26 28 ].…”
Section: Methodsmentioning
confidence: 99%